IEEE Congress on Evolutionary Computation 2010
DOI: 10.1109/cec.2010.5586127
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Co-evolution for large scale optimization through more frequent random grouping

Abstract: In this paper we propose three techniques to improve the performance of one of the major algorithms for large scale continuous global function optimization. Multilevel Cooperative Co-evolution (MLCC) is based on a Cooperative Co-evolutionary framework and employs a technique called random grouping in order to group interacting variables in one subcomponent. It also uses another technique called adaptive weighting for co-adaptation of subcomponents. We prove that the probability of grouping interacting variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(83 citation statements)
references
References 10 publications
1
82
0
Order By: Relevance
“…As a fact, all participants of previous competitions on LSGO held at the IEEE Congress on Evolutionary Computation (CEC-2008, CEC-2010 and CEC-2012), except [15], simply used RNGs as initialization methods. Considering the growing demands on solving LSGO problems [16], [17], it is important to investigate whether advanced initialization methods are able to improve the performance of state-of-theart EAs in comparison to basic RNGs.…”
Section: Introductionmentioning
confidence: 99%
“…As a fact, all participants of previous competitions on LSGO held at the IEEE Congress on Evolutionary Computation (CEC-2008, CEC-2010 and CEC-2012), except [15], simply used RNGs as initialization methods. Considering the growing demands on solving LSGO problems [16], [17], it is important to investigate whether advanced initialization methods are able to improve the performance of state-of-theart EAs in comparison to basic RNGs.…”
Section: Introductionmentioning
confidence: 99%
“…MLCC [32] is further improved by Yang et al [14]. They introduced 3 techniques to improve its performance.…”
Section: Yang Et Al Proposed Mlccmentioning
confidence: 99%
“…Random grouping has been proposed to increase the performance on non-separable high dimensional problems (Omidvar et al 2010;Yang et al 2008). With random grouping, the parameters are frequently regrouped to increase the chance of having interacting parameters in the same subproblem.…”
Section: Cooperative Coevolutionary Algorithmmentioning
confidence: 99%
“…CC has a good performance especially on large-scale optimisation problems. Though, other works (Li and Yao 2009;Omidvar et al 2014Omidvar et al , 2010Potter and De Jong 1994;Ray and Yao 2009;Yang et al 2008) found that the CC struggles to solve non-separable problems (i.e. interactions/interdependencies between parameters).…”
Section: Introductionmentioning
confidence: 99%